Everyone in the Bible - Barker, William Pierson (Westwood, N.J., F.H. Revell Co., 1966)
The purpose of this volume is to provide Bible readers with a concise, accurate, and readable biographical account of every person named in the Bible.
Keywords: Bible -- Biography